Picosecond laser induced wettability modification of PC-PMMA polymer blends - Shi, Xiang (2014)
In this project, the effect of laser parameters on wettability of polycarbonate (PC), poly(methyl methacrylate) (PMMA) and polycarbonate-Poly(methyl methacrylate) (PC-PMMA) polymer blend were investigated. The effect of fluence and power deposition rate(PDR) has been discussed. Experiment was first conducted on pure PC, concluded both fluence and PDR could influence the surface wettability. Subsequently, the ranges of fluence and PDR were found. After that, two fluence values (3520 mJ/cm2 and 7040 mJ/cm2) and two PDR values (0.70 J/mm2 and 1.40 J/mm2) were selected for further investigation on polymer blends experiments. In the polymer blends experiment, it was found that water contact angles (WCAs) increased dramatically under the influence of fluence or PDR. Furthermore, under the specific fluence and PDR, WCA had the linear relationship with the composition of polymer blends. Therefore, it was concluded material composition could also influence the surface wettability.